The trend of open access in science and technology activites and some proposals for Vietnam - Ha Cong Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Open Access in science and technology (S&T) activities has been a strong development trend in the world over the past two decades due to the benefits it brings to the scientific community and society. Recommendation on Open Science of the United Nations Educational, Scientific and Cultural Organization (UNESCO) adopted at the General Conference held in November 2021, identified open access is one of four key pillars aimed at making scientific knowledge open, accessible and reusable to anyone, increasing scientific collaboration and information sharing for the benefit of S&T and society. This article focuses on analyzing and clarifying the concept and methods of open access, specifying development trends and impacts of open access on stakeholders in science and technology activities, assessing the current situation of open access in Vietnam, from there, propose some directions for developing open access in Vietnam in the coming period. Code: 23081701